Ancient hastisetae of Cretaceous carrion beetles (Coleoptera: Dermestidae) in Myanmar amber. Issue 6 (November 2016) - Poinar, George; Poinar, Roberta
Abstract: Hastisetae are extremely elaborate and intricate insect setae that occur solely on dermestid larvae (Coleoptera: Dermestidae). The present work characterizes hastisetae found in mid-Cretaceous amber from Myanmar and compares them to hastisetae found on extant dermestid larvae. The presence of hastisetae in Myanmar amber shows that lineages of dermestid beetles had already developed hastisetae by the mid-Cretaceous and their presence allows us to follow the evolutionary development of this particular arthropod structure over the past 100 million years. Hastisetae attached to a parasitic wasp in the same piece of amber indicates that ancient dermestid beetles used their hastisetae for defense, similar to their function today. Highlights: Ancient hastisetae 100 million years old are reported from Myanmar amber. Ancient hastisetae establish lineages of the family Dermestidae in the mid-Cretaceous. Detailed structure of ancient hastisetae are provided. Presence of ancient hastisetae in contact with a parasitic wasp suggests they were used for defense in the mid-Cretaceous. Ancient hastisetae are compared to those of extant dermestid larva.